2000
DOI: 10.1103/physrevlett.85.3560
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Periodic Melting Point Observations for Nanostructure Ensembles

Abstract: We report a study of the thermodynamic properties of indium clusters on a SiN (x) surface during the early stages of thin film growth using a sensitive nanocalorimetry technique. The measurements reveal the presence of abnormal discontinuities in the heat of melting below 100 degrees C. These discontinuities, for which temperature separation corresponds to a spatial periodicity equal to the thickness of an indium monolayer, are found to be related to the atomic "magic numbers," i.e., the number of atoms necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 28 publications
4
69
0
Order By: Relevance
“…Allen and co-workers developed a suitable experimental technique to study the calorimetry of the melting process in nanoparticles and found that both the melting temperature and the latent heat of fusion depend on the particle size. [38][39][40] Here we calculate the molar heat of fusion and molar entropy of fusion for Ag nanoparticles, and the results are shown in Fig. 9.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Allen and co-workers developed a suitable experimental technique to study the calorimetry of the melting process in nanoparticles and found that both the melting temperature and the latent heat of fusion depend on the particle size. [38][39][40] Here we calculate the molar heat of fusion and molar entropy of fusion for Ag nanoparticles, and the results are shown in Fig. 9.…”
Section: Silver Nanoparticlesmentioning
confidence: 99%
“…Due to the small thermal mass of the sensors, very fast heating rates can be achieved that minimize heat loss to the environment. For instance, the nanocalorimetry sensor originally developed by Allen and coworkers can attain heating rates as large as 10 5 K/s and has been used to perform very precise heat capacity measurements on nanoparticles 3,4 and ultrathin polymer films. [5][6][7] Schick et al have developed a different sensor that can operate under non-adiabatic conditions with controlled heating and cooling rates in the range of 10 3 K/s.…”
Section: Introductionmentioning
confidence: 99%
“…This type of sensor has the capability of measuring incremental changes in sample thickness of the order of 0.004 nm [12]. It should be noted that in previous nanocalorimetry experiments involving thin metal films, [9][10][11][12], the thickness of the membrane was about 30-50 nm. The sensors used in this work have a 10-fold increase of membrane thickness.…”
Section: Methodsmentioning
confidence: 99%
“…The operation and fabrication of the nanocalorimetry device and technique are described in detail elsewhere [7][8][9][10][11][12]. Here we give an abridged description of the technique.…”
Section: Methodsmentioning
confidence: 99%